(untitled) (Revista Lusófona de Educação, 2026)
From the outset, Paulo Freire identified himself as a humanist educator. While his proposal for a humanizing education was gaining admirers and adherents around the world, philosophical humanism was simultaneously becoming the target of strong and incisive criticism. Given that Freire’s work remains influential in contemporary educational debates, it is important to clarify the meaning of his humanism in order to prevent misunderstandings that may hinder a proper understanding of his pedagogical proposal. In this context, the present essay turns to the theoretical and philosophical foundations of Freire’s educational thought, with particular attention to the concept of humanism. Drawing on bibliographic research, it seeks to contrast Freire’s conception of humanism with traditional philosophical humanism—especially modern humanism—in order to evaluate the implications of anti-humanist critique in his approach. Centering the analysis on the underlying conception of the human being in traditional philosophical humanism, the study identifies a clear departure by Freire from the metaphysical assumptions that ground this tradition. It concludes that Freirean anthropology incorporates the anti-humanist critique and, from this standpoint, reinterprets traditional humanist categories—such as freedom, autonomy, and ethics—within a post-metaphysical framework.